RUSSIAN AGGRESSION AS A DRIVING FACTOR INFLUENCING THE ACTIVITIES OF THE INTERNATIONAL LABOR ORGANIZATION AND THE TRANSFORMATION OF INTERNATIONAL LABOR LAW - BURKA, ALONA (Ehrlich's Journal, 2023)
Today, Ukrainian society and the world community in general have begun a new stage – the stage of reassessment of universal values and transformation. The impetus for this was Russia’s military action against Ukraine. The changes that await us will not pass any sphere, neither legal, nor economic, nor political, nor cultural, and the basis of these changes have already formed / will be the prevailing ideas and sentiments in society. It is clear that most changes should be expected in Ukraine, but other countries and international organizations will not pass them by, or rather, have not passed. Despite the full scale of research conducted in such areas as: certain aspects of the International Labor Organization, including issues of international standards developed by it, analysis of a number of its conventions; sociological concept of law, the concept of “living law”, today, as a result of the Russian-Ukrainian war, one of the terrible consequences of which is unemployment, millions of labor migration and the need to develop and implement additional guarantees to protect workers, there is a need to study the International Labor Organization subject of international labor law; analyze the factors contributing to the future transformation of the system of international labor law. Today, it is important that the International Labor Organization use its support to work with international financial institutions and governments to promote productive employment. However, analyzing the activities of the organization since February 24, 2022, we can say that after more than two months of war, we would like to see it more active in solving global problems in the field of labor migration and against the background of “undermining” the world labor market . As the International Labor Organization condemns Russian aggression, suspends technical cooperation with Russia, and information policy is just the basics, the smallest minimum that could be. Today, the International Labor Organization must not only be verbally united, but also actively involved in the process of monitoring, control, creating new standards of labor law and the transformation of international labor law in general, based on the problems, needs and interests of the working population.